Open innovation in Aida Furniture UKM in Pasuruan: A study on the influence of entrepreneurial founders on open innovation practices - Suparno; Sudarmiatin; Imam Mukhlis (International Journal of Economics, Business and Innovation Research, 2022)
The purpose of this research is to deepen our knowledge about the role of the "human" Aida Furniture UKM in Pasuruan in adopting Open Innovation. To do this, we examine the characteristics of Aida Furniture SME managers, viz. main founder/CEO. influencing the dynamics of adoption (i.e. mechanism, partners, incentives and sequence of adoption) of open innovation in SMEs. Empirical analysis based on seven case studies of Irish medical device SMEs that have achieved international high growth targets Our results show that examples of open innovation adoption by project-based Furniture SMEs as opposed to organizational reasons and a natural tendency to return to a closed paradigm Through a “switchback” strategy after necessity fulfilled. UKM Furniture Aida, on the other hand, developed project-based open innovation skills and matured as a result. This highlights the importance of the “do, use, interact” learning mode in the development of OI SMEs. In addition, Aida Furniture UKM can embark on a general sequential and temporal path focusing on commercialization through an inside-out mode, followed by a complex co-creation mode. This study also finds that West and Bogers (2014) acquire, integrate and commercialize the framework, and thus extend Upper Echelon Theory (UET), the characteristics of the Founder/CEO. It also provides insight into how that affects OI adoption dynamics. The link between the two is strengthened by the Open Innovation and Entrepreneurship Theory.